Cobalt phosphinates as precursors of cobalt phosphide electrocatalysts - Vílchez-Cózar, Álvaro; Cabeza-Díaz, Aurelio; Bazaga-García, Montse; Visa, Aurelia; Ilia, Gheorghe; Olivera-Pastor, Pascual; Pérez-Colodrero, Rosario Mercedes (My University, 2022)
The scarcity and high cost of Pt and Ru/Ir-based noble metal electrocatalysts forces to design alternative low-cost and efficient materials for sustainable energy storage and conversion technologies. Among them, phosphorus-containing coordination polymers, such as phosphinates, have emerged as potential precursors of transition-metal phosphide (TMP) electrocatalysts. The possibility of incorporating two funtionalized organic moieties into the phosphinate ligands makes metal phosphinates highly attractive precursors to obtain core-shell carbon/TMP electrocatalysts. In this research-work, we report the synthesis and crystal structure of two Co2+-phosphinates derived from the (2-carboxyethyl)(phenyl)phosphinic acid (CEPPA), Co2[(O2P(CH2CH2COO)(C6H5)(H2O)]2·2H2O (CoCEPPA-1D) and Co3[O2P(CH2CH2COO)(C6H5)]2(OH)2 (CoCEPPA-2D), synthesized by microwave-assisted method. These solids were used as precursor of cobalt phosphides (Co2P/CoP) by thermal reduction under 5%H2-Ar atmosphere at different temperatures and their electrocatalytic performances were investigated toward Oxygen Evolution Reaction (OER), Oxygen Reduction Reaction (ORR) and Hydrogen Evolution Reaction (HER). The relationship between Co/P molar ratios and/or the Co2+ coordination environment in the precursor structures and the electrocatalytic activity of the prepared cobalt phosphides will be discussed.
https://qies22.icms.us-csic.es/
Keywords: Compuestos organofosforados; Electroquímica; Catálisis; Cobalt phosphinate; cobalt phosphide; electrocatalysts; 2-carboxyethyl)(phenyl)phosphinic acid (CEPPA); microwave-assisted method; Oxygen Evolution Reaction (OER); Hydrogen Evolution Reaction (HER)